Clothes, condoms, and customer satisfaction: The effect of employee mere presence on customer satisfaction depends on the shopping situation. Issue 6 (22nd April 2018) - Otterbring, Tobias; Lu, Chaoren
Abstract: Few studies have examined how customers respond to the mere presence of others in the shopping environment, and only one article (Söderlund, 2017 ) has investigated the unique impact that employee presence has on key customer outcomes. Söderlund (2017 ) found that customers entering a store with an employee present (vs. absent) reported significantly higher levels of customer satisfaction, with their increased levels of pleasurable feelings mediating this effect. However, similar to the majority of theorizing on customer satisfaction, that article was restricted to data collected in a Western society. Given the rapid economic growth in many Asian regions, there is a need to examine the applicability of such Western‐based findings from an Asian perspective, and hence include participants from Eastern societies. Accordingly, the present research investigated whether Söderlund's (2017 ) results could be replicated among Asian customers. The current work also sought to extend prior findings beyond pleasure and customer satisfaction while simultaneously documenting a boundary condition for the hitherto positive employee mere presence effects. To this end, two between‐subjects experiments with a total sample of 498 Chinese customers were conducted. Study 1, which involved a shopping situation in a clothing store, replicated Söderlund's (2017 ) main results and further found that employee mere presence (vs. absence) had a significant positive impact on customers' loyalty intentions. These results were reversed in Study 2, in which the shopping situation involved the purchase of an embarrassing product. Under such circumstances, employee presence (vs. absence) consistently produced negative effects on customers' levels of pleasure, satisfaction, and loyalty intentions.